Nontrivial Solutions for the 2nth Lidstone Boundary Value Problem - Yaohong Li; Jiafa Xu; Yongli Zan (Journal of Mathematics)
In this paper, we study the existence of nontrivial solutions for the 2nth Lidstone boundary value problem with a sign-changing nonlinearity. Under some conditions involving the eigenvalues of a linear operator, we use the topological degree theory to obtain our main results.